The General Form of Normal Quasi-Differential Operators for First Orderand Their Spectrum - (:unkn) unknown (My University, 2018)
In this work, the general form of all normal quasi-differential operators for first order in the weightedHilbert spaces of vector-functions on right semi-axis in term of boundary conditions has been found. Later on,spectrum set of these operators will be investigated.